Perception of COVID-19 and Vaccine Acceptance among Healthcare Workers - Nemr, Nader; Kishk, Rania M.; Soliman, Nourhan Hassan; Farghaly, Rasha Mohammed; Kishk, Safaa M.; Louis, Nageh (International Journal of Microbiology, 2022)
Background. COVID-19 infection is more likely to be acquired and transmitted by healthcare workers (HCWs). Furthermore, they serve as role models for communities in terms of COVID-19 vaccination attitudes. As a result, HCWs’ reluctance to vaccinate could have a significant impact on pandemic containment efforts. Aim. To characterize the current COVID-19 vaccine approval situation among healthcare workers and to determine the most likely reason for agreement or disagreement with COVID-19 vaccination. Methods. This cross-sectional design included 451 HCWs from COVID-19 treatment institutions, with COVID-19 exposure risk changing depending on job function and working location. Results. The study recruited 156 physicians and 295 nurses, of whom 58.1% were female and 41.9% were male. Physicians had a significantly higher rate of participation in COVID-19 pandemic prevention and control, with a rate of 69.9% versus 55.3% of nurses. Acceptance of COVID-19 vaccination was reported by 40.8% of HCWs. The rate of acceptance was significantly higher among physicians (55.1%) than among nurses (33.2%) (p<0.001). Most HCWs (67.8%) believed the vaccine was not effective. Physicians showed more significant trust in the effectiveness of the vaccine than nurses (41% and 27.5, respectively) (p=0.003). Concerning vaccine safety, only 32.8% of HCWs believed it was safe. This was significantly higher in physicians (41.7%) than in nurses (28.1%) (p=0.004). Conclusion. Vaccination uncertainty is common among healthcare personnel in Egypt, and this could be a significant barrier to vaccine uptake among the public. Campaigns to raise vaccine knowledge are critically needed.